An investigation of the government export assistance programmes on firm's performance: A study of SMES in Malaysia / Fathin Nabihah Sapee - Sapee, Fathin Nabihah (Faculty of Business Management, 2015)
SMEs presence is significant nowadays to most economies, particularly those from emerging countries. The internationalization of these firms is no longer an option, it is indeed necessary for them to follow the wave of globalization. Despite of their constraints, Malaysian SMEs are struggling to expand into international market and compete internationally to sustain their foothold in the country. Various factors have forced SMEs in Malaysia to engage internationally, however the venture are difficult to be accomplished independently. As a result, the Malaysian government has initiated various efforts in supporting them to stand in the international arena. Many agencies have been established and numerous programmes have been developed to encourage SMEs internationalization. This study aims to investigate whether the following constructs, awareness of export assistance programmes among SMEs in Malaysia, satisfaction among SMEs with the programmes provided and benefit of export assistance programmes would have a relationship with the firms' performance. Using the email questionnaire technique, a survey was conducted among SMEs in Malaysia. In total, 500 questionnaires were distributed, 89 completed questionnaires were received back within the period of four weeks. The demographic profile of the respondents were discussed and presented. Next, in determining the relationship between awareness, satisfaction and benefit of the export assistance programmes on firms' performance, regression analysis was performed. In terms of the relationship between awareness and performance, satisfaction and performance as well as between benefit and performance, the results indicated that all of them are significantly related to performance where satisfaction makes the strongest unique contribution to explain the firms' performance.